To kill and to die: On the joys and sorrows of juvenile drug dealers in Bahia, Brazil - Zoettl, P. A. (Critical Sociology, 2023)
This article discusses the life and death of juvenile drug dealers in the state of Bahia, Brazil, where the drug business has become omnipresent and a growing number of youths from the urban periphery are taking up a career with one of the country’s many drug gangs. The price most of them pay for their economic success as traffickers is high: they are repeatedly imprisoned under harsh conditions, suffer severe physical violence and, at times, die at young age. Drawing on the narratives of juveniles from Bahia and the writings of Bataille and Baudrillard, the youths’ approach to life is discussed as a knowingly illusory attempt to regain their sovereignty within the boundaries of consumer capitalism. It is argued that their death is not a blow of fate, but rather the premeditated consequence of their acquisition of consumer-citizenship ‘on credit’ and, ultimately, their refusal to constitute Brazil’s modern precariat.